PENGARUH AKTIVITAS LITERASI MATEMATIKA TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA KELAS IV - Pambudi, Rilo Eko; Soekirno, Soewalni; Prihastari, Ema Butsi (JURNAL SINEKTIK, 2020)
Research aimed to determine the influence of mathematical literacy activities on the ability of critical thinking in class IV mathematics of State Elementary School 3 Karanganyar where the research was conducted in the elementary School of Negeri 3 Karanganyar. This research sample was a class IV student numbering 36 children. This type of research used quantitative types. Data collection Techniques used: (1) tests; (2) Observation; (3) Documentation; (4) interviews. The data analysis technique used is the technique of Paired sample T-Test. Based on the results of the test Paired sample T-Test obtained that the value of Thitung 24.24 > This at a rate of significance 5% of 1.69. Thus, there is the influence of mathematical literacy activities on the ability of critical thinking in class IV mathematics of State Elementary School 3 Karanganyar Year lesson 2019/2020 can be accepted the truth in a significant. Summed up, implementing mathematical literacy activities can help develop critical thinking skills. It is recommended to implement mathematical literacy practice activities. For learners to solve mathematical problems with critical thinking skills.